Transcription Start Site Mapping And Small Regulatory Rna Profiling Of Mycobacterium Tuberculosis - Cheah, Hong Leong (2022)
Mycobacterium tuberculosis is an actinobacterium that causes chronic infections. Its pathogenesis lies in the thick, lipid-rich cell envelope that facilitate persistence in hostile environments. A refined knowledge of regulatory networks within M. tuberculosis is important to understand its pathogenesis for therapeutic design. Small regulatory RNAs (sRNAs) are key modulatory components within all organisms. Extensive studies over the past decade have uncovered a plethora of bacterial sRNAs, implying that bacterial transcriptomes are far more sophisticated than previously anticipated. Here, sRNA profiles of M. tuberculosis exposed to different stresses were established by analyzing RNA-seq data to address different facets of sRNAome in M. tuberculosis. This study has identified a total of 1,376 sRNA candidates and the subsequent 5’/3’RACE assay has successfully validated a total of five sRNAs, among which predictedRNA_0578 may encode for a novel small peptide and predictedRNA_0020 potentially affects the formation of mycobacterial cell wall. Besides, this study also included transcription start site (TSS) landscapes that provide additional transcriptional features, e.g., promoters and untranslated regions (UTRs). Taken together, this study reveals the complexities of the mycobacterial sRNAome and may facilitate the development of antisense antibiotics.